Removal of Copper Ions from Waters Using Surfactant-Enhanced Hybrid PAC/MF Process - Basar, Canan Akmil; Aydiner, Coskun; Kara, Serdar; Keskinler, Bülent (Asce-Amer Soc Civil Engineers, 2009)
This paper deals with the removal of copper ions from aqueous solutions by using surfactant-enhanced powdered activated carbon (PAC)/microfiltration (MF) hybrid process, including the evaluation of process performance and fouling dynamics at various linear alkyl benzene sulfonate (LABS), PAC, and Cu2+ concentrations of feed solution. Although the use of surfactant as an additive material increased the adsorption efficiency in PAC/MF hybrid process, a considerable amount of the flux was lost for surfactant concentration above critical micelle concentration. The process could be employed with a performance of 74.7%, 97.2% and 87 L/m(2) h for LABS rejection, Cu2+ rejection and permeate flux at the conditions of 2 g PAC/L, 5 mM LABS, 0.2 mM Cu2+, and 60-min process time. Cu2+ rejection, which increased with increasing of LABS, and PAC amounts decreased with the increase in Cu2+ concentration. It was understood that the increments in LABS, PAC, and Cu2+ concentrations being an indicator for the feed solution quality led to the occurrence of more fouling on the membrane. The analyses of dynamics concerning the fouling behaviors, which were carried out using single and combined pore blocking models, put forward that the cake formation was the main predominant mechanism in the process. It was also determined that the variation of feed contents deduced the presence of rather complex fouling behaviors as a simultaneous function of secondary membrane layer formation and clogging and narrowing of membrane pores by surfactants.
Keywords: Cross-Flow Microfiltration; Long-Term Operation; Waste-Water; Membrane Bioreactor; Activated Carbon; Filtration Characteristics; Photocatalytic Oxidation; Cellulose-Acetate; Virus Removal; Metal-Ions